1998
DOI: 10.1097/00005176-199804000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Extensively Hydrolyzed Casein-Whey Protein Formula in Immediate Cow's Milk Protein Hypersensitivity

Abstract: This extensively hydrolyzed casein-whey protein formula is generally safe to feed children with immediate hypersensitivity to cow's milk. However. it is advisable that the first intakes be given under direct medical supervision, in that the occurrence of adverse reactions in highly sensitive infants cannot be unequivocally excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…Furthermore, as also mentioned by Martin‐Esteban et al. (20) the results of this kind of study are strongly dependent on the type of study population. The guidelines are drawn up to be generalized for the overall population, but the studies are usually performed in specialized hospitals, in which the population of children is often more seriously affected by CMA.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Furthermore, as also mentioned by Martin‐Esteban et al. (20) the results of this kind of study are strongly dependent on the type of study population. The guidelines are drawn up to be generalized for the overall population, but the studies are usually performed in specialized hospitals, in which the population of children is often more seriously affected by CMA.…”
Section: Discussionmentioning
confidence: 56%
“…A recent study conducted by Martin‐Esteban et al. (20) with a casein‐whey protein hydrolysate formula, was also performed according to the current guidelines. However, 50% of the children were fed the tested formula before the challenge.…”
Section: Discussionmentioning
confidence: 99%
“…The figure of 10% appears to be derived from the statement that for a formula to be considered hypoallergenic at least 90% of cows milk allergic children must tolerate the product and the actual proportion of children intolerant to EHF may be less than this 5 . Thus the combined results of three studies of EHF in children with IgE‐mediated or non‐IgE‐mediated cows milk protein allergy found that 97% (126/130) tolerated EHF 5–7 . There is a small group of children with multiple food protein hypersensitivity some of whom do not tolerate EHF; however, it is unclear what proportion of the total cows milk allergic patients this comprises.…”
Section: Discussionmentioning
confidence: 99%
“…5 Thus the combined results of three studies of EHF in children with IgE-mediated or non-IgE-mediated cows milk protein allergy found that 97% (126/130) tolerated EHF. [5][6][7] There is a small group of children with multiple food protein hypersensitivity some of whom do not tolerate EHF; however, it is unclear what proportion of the total cows milk allergic patients this comprises. A hospital-based specialist paediatric allergy unit identified approximately 60 such patients over 10 years with suspected late adverse reactions to formulae including cows milk, soy and protein hydrolyzate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been recommended that a formula should be called ‘hypoallergic’ if it is tolerated by at least 90% (with 95% confidence) of the infants with CMA [18]. These criteria have been met by some extensive hydrolysates [9,19] and amino acid mixtures [10].…”
Section: Introductionmentioning
confidence: 99%